E-MODUL AJAR BERBASIS PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DALAM MATERI ALJABAR PADA SISWA KELAS VII - Elwita Nafa Fitria; Yadi Ardiawan; Hartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to produce teaching e-modules based on problem-based learning (pbl) on mathematical problem solving skills in algebra material for seventh grade students that are valid, practical, and effective. The research method used is research and development with the ADDIE development model or commonly called the research and development (R&D) method which consists of Analysis, Design, Development, Implementation and Evaluation. The findings of this study successfully developed a problem based learning e-module. The developed e-module has been validated by media experts and material experts. The validation results show that this e-module is suitable for use without revision. The e-module trial was carried out on class VII students of Assalam Islamic Boarding School Middle School. Judging from the results of student response questionnaires and teacher response questionnaires, the level of practicality of this e-module is very practical. Based on the results of the posttest of seventh grade students, it can be concluded that the e-module developed is effective. The implication of this research is that in order for e-modules to be developed in other materials and subjects, training should be conducted for teachers on how to create and use e-modules that can attract students' interest in learning and give positive value to the use of smartphones.